Preparation process of green flame-retardant plywood
Through the preparation process of green flame retardant plywood, advanced preparation technology and environmentally friendly materials are used to solve the problems of fire hazards and environmental pollution of traditional artificial board materials, and high-performance and environmentally friendly flame retardant plywood is achieved.
Patent Information
- Application Number
- CN202411958108.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Traditional artificial board materials have fire hazards and environmental pollution problems, especially the release of harmful substances such as formaldehyde and phenol, which affects the environment and human health.
The preparation process of green flame retardant plywood is adopted, and advanced preparation technologies such as Diels-Alder reaction method and high-temperature heating method are combined with binary benzoxazine-derived monomers, sodium carboxymethylcellulose, bio-based carbon-forming agents and metal organic frames to prepare plywood with smoke inhibition, low toxicity, environmental protection and excellent flame retardant properties.
It achieves a safe and environmentally friendly flame retardant performance, reduces the release of harmful substances, improves the thermal stability and mechanical strength of the materials, and is suitable for construction, decoration, home and other fields.
Smart Images

Figure CN119704340A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation of a new material, in particular to a preparation process of a green flame-retardant plywood. Background Art
[0002] As people's environmental awareness increases, the environmental performance of the wood-based panel industry has become an important consideration for consumers when purchasing. At the same time, wood is flammable, and the use of wood-based panels in building decoration and renovation poses a fire hazard. With the implementation of relevant laws and regulations and standard systems for flame retardant materials in my country, higher requirements are placed on flame retardant materials. The flame retardant performance of wood-based panels has become one of the main factors for consumers to choose. Although traditional synthetic resin adhesives based on petrochemical products have excellent performance in bonding performance and water resistance, the harmful substances such as formaldehyde and phenol they release pose a potential threat to the environment and human health. Therefore, the research and development of safe, environmentally friendly, green flame-retardant plywood has become a key direction for the transformation and upgrading of the industry.
[0003] At the same time, as the main raw material of artificial boards, the flammability of wood makes the application of artificial boards in the fields of construction and decoration have certain safety hazards. With the continuous improvement of the relevant laws and regulations and standards of the country on flame retardant materials, more stringent requirements are put forward for the flame retardant properties of artificial boards. By creatively combining advanced preparation technologies such as Diels-Alder reaction method and high-temperature heating method, and having the following characteristics: (1) smoke suppression, (2) low toxicity, (3) environmental protection and excellent flame retardant properties, it provides strong support for its wide application in many fields such as construction, decoration, and home furnishing. Summary of the invention
[0004] In view of the above problems, the present invention provides a preparation process of green flame retardant plywood.
[0005] The invention provides a preparation process of green flame retardant plywood, comprising the following steps: preparation of dioxane, preparation of vanillic acid-furfurylamine benzoxazine (VF), preparation of binary benzoxazine derivative monomers, preparation of refined sodium carboxymethyl cellulose (CMC), preparation of water-soluble bio-based carbon-forming agent, preparation of smoke-suppressing and low-toxic flame retardant liquid PAP-Mg-Na, preparation of complex flame retardant PAP-Ly-Mg, and preparation of MOF (metal organic framework) flame retardant composite materials.
[0006] Wherein, step (3) preparation of binary benzoxazine derivative monomer
[0007] First, a certain amount of phenylphosphate bismaleimide is weighed using an electronic analytical balance and subjected to a Diels-Alder reaction. Then, a small amount of furfuryl alcohol resin and a small amount of vanillic acid-furfurylamine benzoxazine (VF) in step (2) are weighed, mixed together in a transparent glass vial and ultrasonically stirred, and then placed in an oven at high temperature to obtain a binary benzoxazine derivative monomer;
[0008] Step (6) Preparation of smoke-suppressing, low-toxicity, flame-retardant liquid PAP-Mg-Na
[0009] First, PAPEMP (polyamino polyether methylene phosphonic acid) was used as an organic ligand to prepare a ligand solution. The metal salt MgCl2·6H20 was dissolved in tap water to obtain a metal solution. The two solutions were then mixed in a certain mass ratio and stirred at room temperature. The water-soluble bio-based carbon-forming agent in step (5) was then added to promote the ligand to react with the metal ion Mg. 2+ A complexing reaction occurs to obtain a complexing solution, and then a NaOH promoting solution is added and slowly added to the complexing solution with stirring to obtain a smoke-suppressing, low-toxic, flame-retardant liquid PAP-Mg-Na;
[0010] Preferably, step (1) preparation of dioxane
[0011] In a round-bottom flask, add a certain amount of diethylene glycol and anhydrous copper sulfate, heat the reaction flask to keep it boiling, control the heating for a period of time, and after the reaction is completed, cool to room temperature, add a large amount of diethylene glycol to the reaction flask, continue heating, collect distillate, add a small amount of concentrated hydrochloric acid to the distillate, and then reflux to remove acetal impurities, separate the water layer after post-treatment, dry the oil layer, and collect the distillate by distillation to obtain dioxane;
[0012] Step (2) Preparation of vanillic acid-furfurylamine benzoxazine (VF)
[0013] A small amount of dioxane, furfurylamine and a small amount of paraformaldehyde from step (1) are added to a three-necked flask in sequence, and then a certain amount of toluene / ethanol mixed solution is added, and the raw materials are uniformly mixed by stirring, and then refluxed at high temperature for a period of time to obtain vanillic acid-furfurylamine benzoxazine (VF);
[0014] Step (3) Preparation of binary benzoxazine derivative monomer
[0015] A small amount of phenylphosphate bismaleimide is dissolved in a certain amount of methyl sulfoxide, subjected to Diels-Alder reaction, cooled to room temperature, and slowly dissolved in the vanillic acid-furfurylamine benzoxazine (VF) in step (2) at high temperature in a three-necked flask equipped with N inlet and outlet, magnetic stirring and water separation and condensation device to obtain a binary benzoxazine derivative monomer;
[0016] Step (4) Preparation of refined sodium carboxymethyl cellulose (CMC)
[0017] The concentrated nitric acid is diluted with anhydrous ethanol to obtain a nitric acid ethanol solution, a small amount of CMC powder (sodium carboxymethyl cellulose) is weighed, and the CMC powder (sodium carboxymethyl cellulose) is dissolved in the nitric acid ethanol solution and filtered after reaction. The insoluble matter obtained at this time is CMC-H. The CMC-H is washed with deionized water for many times. The above CMC-H is added to a high concentration of sodium hydroxide solution and stirred thoroughly to obtain a viscous transparent liquid. At this time, CMC-H reacts with sodium oxide to generate CMC (sodium carboxymethyl cellulose). CMC (sodium carboxymethyl cellulose) is viscous in water. A large amount of the dibenzoxazine derivative monomer in step (3) is added to obtain a white flocculent, which is CMC (sodium carboxymethyl cellulose). The CMC (sodium carboxymethyl cellulose) is washed with an ethanol solution for many times until the pH is neutral, and then dried in a vacuum oven to constant weight. After crushing, refined sodium carboxymethyl cellulose (CMC) is obtained;
[0018] Step (5) Preparation of water-soluble bio-based carbon-forming agent
[0019] Melamine (MA) and vanillin are added to a flask in a certain ratio, and then dimethylformamide (DMF) solvent is added, and the reaction is stirred. After the reaction is complete, the reaction temperature is increased until dimethylformamide (DMF) is volatilized, and the solution after the reaction is poured out and dried to obtain a bio-based carbon-forming agent carbon coating (MV). The refined sodium carboxymethyl cellulose (CMC) in step (4) is added to a beaker, and the solution is stirred to mix evenly. Ammonium polyphosphate (APP) is added and stirred thoroughly. Finally, the obtained solution is dried, and the solution is crushed to obtain a water-soluble bio-based carbon-forming agent;
[0020] Step (6) Preparation of smoke-suppressing, low-toxicity, flame-retardant liquid PAP-Mg-Na
[0021] First, PAPEMP (polyamino polyether methylene phosphonic acid) was used as an organic ligand to prepare a ligand solution. The metal salt MgCl2·6H20 was dissolved in tap water to obtain a metal solution. The two solutions were then mixed in a certain mass ratio and stirred at room temperature. The water-soluble bio-based carbon-forming agent in step (5) was then added to promote the ligand to react with the metal ion Mg. 2+ A complexing reaction occurs to obtain a complexing solution, and then a NaOH promoting solution is added and slowly added to the complexing solution with stirring to obtain a smoke-suppressing, low-toxic, flame-retardant liquid PAP-Mg-Na;
[0022] Step (7) Preparation of complex flame retardant PAP-Ly-Mg
[0023] Lysine, ammonium polyphosphate (APP) and melamine are added into a four-necked flask in a certain molar ratio, mixed and stirred, heated to a high temperature by a constant temperature digital display heating jacket, and a small amount of smoke-suppressing and low-toxic flame-retardant liquid PAP-Mg-Na prepared in step (6) is added, and chitosan and vitamin B are added, and after curing and ripening reaction, the mixture is crushed to obtain a complex flame retardant PAP-Ly-Mg;
[0024] Step (8) Preparation of MOF (metal organic framework) flame retardant composite materials
[0025] A small amount of dry MOFs (metal organic framework) nanoparticles is ultrasonically dispersed in an ethanol solution, and then the complex flame retardant PAP-Ly-Mg in step (7) is added to the above liquid, allowed to stand, and then added to the cellulose dispersion, vigorously stirred at room temperature, the mixed solution is drained through a Buchner funnel, and then dried in a vacuum oven to obtain a MOF (metal organic framework) flame retardant composite material.
[0026] Preferably, step (1) preparation of dioxane
[0027] In a 250-500mL round-bottom flask, add 100-200g of diethylene glycol and 2-5g of anhydrous copper sulfate, heat the reaction flask to keep it boiling, control the heating for 1-5h, after the reaction is completed, cool to room temperature, add 105-200g of diethylene glycol to the reaction flask, continue heating, collect the distillate, add 10-20mL of concentrated hydrochloric acid to the distillate, and then reflux to remove acetal impurities, separate the water layer after post-treatment, dry the oil layer, and distill and collect the distillate with a boiling point of 100-200°C to obtain dioxane.
[0028] The advantage of the present invention is that diethylene glycol is used as a starting material, dehydration condensation is carried out under the catalytic action of anhydrous copper sulfate to generate an intermediate containing an epoxy group, and further reaction is performed to form the target product dioxane, thereby changing the more dangerous and expensive reagents used in the traditional synthesis route, and by-product impurities are effectively removed through distillation, thereby improving the purity of the product and providing an excellent basis for subsequent modification steps.
[0029] Preferably, step (2) preparation of vanillic acid-furfurylamine benzoxazine (VF)
[0030] 16-20 g of the dioxane prepared in step (1), 9-15 g of furfurylamine (0.1-1 mol) and 6-10 g of paraformaldehyde are added to a three-necked flask in sequence, and then 90-100 mL of a toluene / ethanol mixed solution is added. The raw materials are uniformly mixed by stirring, and then refluxed at 80-100° C. for 8-15 h to obtain vanillic acid-furfurylamine benzoxazine (VF).
[0031] The invention has the advantages that, by selecting dioxane, furfurylamine and polyformaldehyde as starting materials and performing a long-time reflux reaction at high temperature, the synthesis path of vanillic acid-furfurylamine benzoxazine (VF) is simplified, the yield and the product purity are improved, and by adopting a toluene / ethanol mixed solvent system, a more environmentally friendly and economically efficient production process is achieved, the reaction conditions are optimized, and the occurrence of side reactions is reduced, which is of great significance to the research and development and industrial application of new materials.
[0032] Preferably, step (3) preparation of a binary benzoxazine derivative monomer
[0033] First, 1-5 g of phenylphosphate bismaleimide is weighed on an electronic analytical balance and subjected to a Diels-Alder reaction. Then, 2-6 g of furfuryl alcohol resin and 1-5 g of vanillic acid-furfurylamine benzoxazine (VF) of step (2) are weighed, mixed together in a transparent glass vial and ultrasonically stirred, and then placed in an oven at 70-90° C. for 24-48 hours to obtain a binary benzoxazine derivative monomer.
[0034] The advantage of adopting the present invention is that the present invention utilizes high temperature for heat preservation treatment, which helps to form a stable six-membered ring structure, provides better thermal stability and mechanical strength, reduces the occurrence of side reactions, ensures the purity and quality of the product, and the Diels-Alder reaction helps to generate a cis addition product.
[0035] Preferably, step (4) is the preparation of refined sodium carboxymethyl cellulose (CMC)
[0036] Concentrated nitric acid is diluted with anhydrous ethanol to a concentration of 25-35% to obtain nitric acid ethanol solution. 10-20g of CMC powder (sodium carboxymethyl cellulose) is weighed and dissolved in the nitric acid ethanol solution. The reaction is carried out for 2-5h and then filtered. The insoluble matter obtained at this time is CMC-H. The CMC-H is washed with deionized water for many times until the pH of CMC-H is 6-10. The above CMC-H is added to a sodium hydroxide solution with a concentration of 40-50% and stirred thoroughly to obtain a viscous transparent liquid. At this time, CMC-H The obtained product is reacted with sodium oxide to generate CMC (sodium carboxymethyl cellulose). CMC (sodium carboxymethyl cellulose) is viscous in water. 100-200 mL of the dibenzoxazine derivative monomer of step (3) is added to obtain a white flocculent product, namely CMC (sodium carboxymethyl cellulose). The CMC (sodium carboxymethyl cellulose) is washed 1-5 times with an ethanol solution having a volume fraction of 70-85% until the pH is neutral, and then dried in a vacuum oven at 100-150°C to constant weight for about 4-10 hours. The refined sodium carboxymethyl cellulose (CMC) is obtained after being crushed.
[0037] The advantages of the present invention are that the present invention is characterized in that the steps of nitric acid ethanol pretreatment and binary benzoxazine derivative monomer post-treatment are introduced, the purification process of CMC (sodium carboxymethyl cellulose) is optimized, its molecular structure is changed by chemical modification, and its physical and chemical properties are enhanced. The nitric acid ethanol treatment helps to remove impurities and adjust the functional group distribution of CMC (sodium carboxymethyl cellulose), while the combination with the binary benzoxazine derivative monomer gives CMC (sodium carboxymethyl cellulose) a new cross-linking structure, thereby improving the mechanical strength and thermal stability of the material.
[0038] Preferably, in step (5), the preparation of a water-soluble bio-based carbon-forming agent
[0039] Melamine (MA) and vanillin are added to a flask at a ratio of 1-5:2-5, and then 10-20g of dimethylformamide (DMF) solvent is added, and the reaction is stirred for 2-5h. After the reaction is complete, the reaction temperature is increased until the dimethylformamide (DMF) is volatilized, and the solution after the reaction is poured out and dried to obtain a bio-based carbon-forming agent carbon coating (MV). 10-20g of the refined sodium carboxymethyl cellulose (CMC) in step (4) is added to a beaker, and the solution is stirred to mix evenly. Ammonium polyphosphate (APP) is added at a ratio of 1-5:1-5, and the mixture is stirred for 1-5h. Finally, the resulting solution is dried, and the solution is crushed to obtain a water-soluble bio-based carbon-forming agent.
[0040] The advantage of adopting the present invention lies in that the present invention is characterized in that it combines organic synthesis and physical mixing technology, constructs a composite material with excellent thermal stability and carbon-forming performance through chemical reaction, and the reaction of melamine (MA) and vanillin generates a carbon coating with rich aromatic structure and three-dimensional network, which enhances the thermal stability of the material, while the introduction of refined sodium carboxymethyl cellulose (CMC) and ammonium polyphosphate (APP) improves the water solubility and processing performance of the material.
[0041] Preferably, step (6) preparation of smoke-suppressing, low-toxicity, flame-retardant liquid PAP-Mg-Na
[0042] First, PAPEMP (polyamino polyether methylene phosphonic acid) is used as an organic ligand to prepare a 50-70 wt% ligand solution, and the metal salt MgCl2·6H20 is dissolved in tap water to obtain a 20-50 w% metal solution. The two solutions are then mixed in a mass ratio of 1-5:1-5, stirred at room temperature for 30-60 min, and then 10-20 g of the water-soluble bio-based carbon-forming agent in step (5) is added to promote the ligand to react with the metal ion Mg. 2+ A complexing reaction occurs to obtain a complexing solution, and then a NaOH promoting solution is added and slowly added to the complexing solution and stirred for 10-60 minutes to obtain a smoke-suppressing, low-toxicity, flame-retardant liquid PAP-Mg-Na.
[0043] The advantage of adopting the present invention is that the present invention utilizes the unique molecular structure of PAPEMP (polyaminopolyether methylenephosphonic acid) to form a stable complex with magnesium ions, and combines with a bio-based charring agent to enhance the charring and smoke suppression performance of the material, improve the thermal stability and flame retardant efficiency of the product, ensure the occurrence of efficient complexation reaction, reduce the excellent water solubility and low toxicity of the product, and contribute to the development of high-performance, environmentally friendly flame retardant materials, which are suitable for the fireproof modification and smoke suppression needs of various polymer systems.
[0044] Preferably, step (7) preparation of complex flame retardant PAP-Ly-Mg
[0045] Lysine, ammonium polyphosphate (APP) and melamine are added into a four-necked flask in a molar ratio of 1-5:2-5:3-5, mixed and stirred, heated to 300-600°C with a constant temperature digital display heating mantle, added with 10-50 mL of the smoke-suppressing and low-toxic flame-retardant liquid PAP-Mg-Na in step (6), and then added with 10-50 g of chitosan and vitamin B, and after curing, ripened for 60-120 min, and crushed to obtain a complex flame retardant PAP-Ly-Mg.
[0046] The advantages of the present invention are that the present invention utilizes the synergistic effect of lysine, ammonium polyphosphate (APP) and melamine, combines the complexing performance of PAP-Mg-Na, and constructs a composite material with excellent thermal stability and flame retardant effect; the mechanical strength and heat resistance of the material are enhanced through high-temperature treatment and chemical cross-linking between components; the bio-based components such as chitosan and vitamin B are introduced, the biocompatibility and environmental protection characteristics of the material are improved, and it is helpful to develop high-performance and multifunctional flame retardant materials, which are suitable for application fields with high requirements for safety and environmental protection.
[0047] Preferably, step (8) preparation of MOF (metal organic framework) flame retardant composite material
[0048] 0.1-0.5 g of dried MOFs (metal organic framework) nanoparticles are ultrasonically dispersed in 30-60 mL of ethanol solution, and then 10-50 mL of the complex flame retardant PAP-Ly-Mg in step (7) is added to the above liquid, and the mixture is allowed to stand for 30-60 minutes. It is then added to 150-300 mL of cellulose dispersion and vigorously stirred at room temperature for 4-10 hours. The mixed solution is drained of water through a Buchner funnel and then dried in a vacuum oven at 80-100° C. for 24-48 hours to obtain a MOF (metal organic framework) flame retardant composite material.
[0049] The present invention has the advantages that it utilizes the high specific surface area and porosity characteristics of MOFs, combines the excellent flame retardant properties of PAP-Ly-Mg, constructs a composite material with high-efficiency flame retardant and smoke suppression functions, changes the preparation method of traditional composite materials, ensures uniform distribution and close contact between components through ultrasonic dispersion and vigorous stirring, enhances the overall stability and mechanical strength of the material, introduces PAP-Ly-Mg as a functional filler, and improves the thermal stability and flame retardant effect of the composite material.
[0050] In summary, the present invention has the following beneficial effects:
[0051] 1. The present invention has the advantages that, by using diethylene glycol as a starting material, dehydration condensation is carried out under the catalytic action of anhydrous copper sulfate to generate an intermediate containing an epoxy group, which is further reacted to form the target product dioxane, thereby changing the more dangerous and expensive reagents used in the traditional synthesis route, and by-product impurities are effectively removed by distillation, thereby improving the purity of the product and providing an excellent basis for subsequent modification steps.
[0052] 2. The advantages of the present invention are that the present invention simplifies the synthesis path of vanillic acid-furfurylamine benzoxazine (VF) by selecting dioxane, furfurylamine and polyformaldehyde as starting materials and refluxes for a long time at high temperature to improve the yield and product purity. In addition, by adopting a toluene / ethanol mixed solvent system, a more environmentally friendly and economically efficient production process is achieved, the reaction conditions are optimized, and the occurrence of side reactions is reduced, which is of great significance to the research and development of new materials and industrial applications.
[0053] 3. The advantage of the present invention is that the present invention uses high temperature for heat preservation treatment, which helps to form a stable six-membered ring structure, provides better thermal stability and mechanical strength, reduces the occurrence of side reactions, ensures the purity and quality of the product, and the Diels-Alder reaction helps to generate cis-addition products.
[0054] 4. The advantages of the present invention are that the present invention is characterized by introducing nitric acid ethanol pretreatment and binary benzoxazine derivative monomer post-treatment steps, optimizing the purification process of CMC (sodium carboxymethyl cellulose), changing its molecular structure through chemical modification, and enhancing its physical and chemical properties. Nitric acid ethanol treatment helps to remove impurities and adjust the functional group distribution of CMC (sodium carboxymethyl cellulose), while the combination with the binary benzoxazine derivative monomer gives CMC (sodium carboxymethyl cellulose) a new cross-linking structure, thereby improving the mechanical strength and thermal stability of the material.
[0055] 5. The advantage of adopting the present invention lies in that the present invention is characterized by combining organic synthesis and physical mixing technology, constructing a composite material with excellent thermal stability and carbon-forming performance through chemical reaction, the reaction of melamine (MA) and vanillin generates a carbon coating with rich aromatic structure and three-dimensional network, which enhances the thermal stability of the material, and the introduction of refined sodium carboxymethyl cellulose (CMC) and ammonium polyphosphate (APP) improves the water solubility and processing performance of the material.
[0056] 6. The advantage of adopting the present invention is that the present invention utilizes the unique molecular structure of PAPEMP (polyamino polyether methylene phosphonic acid) to form a stable complex with magnesium ions, and combines with a bio-based charring agent to enhance the charring and smoke suppression properties of the material, improve the thermal stability and flame retardant efficiency of the product, ensure the occurrence of efficient complexation reaction, reduce the excellent water solubility and low toxicity of the product, and contribute to the development of high-performance, environmentally friendly flame retardant materials, which are suitable for the fire modification and smoke suppression needs of various polymer systems.
[0057] 7. The advantage of adopting the present invention is that the present invention utilizes the synergistic effect of lysine with ammonium polyphosphate (APP) and melamine, combined with the complexing properties of PAP-Mg-Na, to construct a composite material with excellent thermal stability and flame retardant effect. The mechanical strength and heat resistance of the material are enhanced by high-temperature treatment and chemical cross-linking between components. The introduction of bio-based components such as chitosan and vitamin B improves the biocompatibility and environmental protection characteristics of the material, which is conducive to the development of high-performance, multifunctional flame retardant materials, and is suitable for application fields with high requirements for safety and environmental protection.
[0058] 8. The advantage of the present invention is that it utilizes the high specific surface area and porosity characteristics of MOFs (metal organic frameworks) and combines the excellent flame retardant properties of PAP-Ly-Mg to construct a composite material with high-efficiency flame retardant and smoke suppression functions, which changes the preparation method of traditional composite materials. Ultrasonic dispersion and vigorous stirring are used to ensure uniform distribution and close contact between the components, enhance the overall stability and mechanical strength of the material, and introduce PAP-Ly-Mg as a functional filler to improve the thermal stability and flame retardant effect of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 The present invention is a process flow chart for preparing a green flame retardant plywood. DETAILED DESCRIPTION
[0060] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.
[0061] If not otherwise specified, the technical means used in the examples are conventional means known to those skilled in the art. In addition, all the raw materials used in the examples are known commercial products.
[0062] Example 1
[0063] Step (1) Preparation of dioxane
[0064] In a 250mL round-bottom flask, add 100g of diethylene glycol and 2g of anhydrous copper sulfate, heat the reaction flask to keep it boiling, control the heating for 1h, and after the reaction is completed, cool to room temperature, add 105g of diethylene glycol to the reaction flask, continue heating, collect the distillate, add 10mL of concentrated hydrochloric acid to the distillate, and then reflux to remove acetal impurities, separate the water layer after post-treatment, dry the oil layer, and distill and collect the distillate with a boiling point of 100°C to obtain dioxane;
[0065] Step (2) Preparation of vanillic acid-furfurylamine benzoxazine (VF)
[0066] 16 g of the dioxane prepared in step (1), 9 g of furfurylamine (0.1 mol) and 6 g of paraformaldehyde were added to a three-necked flask in sequence, and then 90 mL of a toluene / ethanol mixed solution was added. The raw materials were uniformly mixed by stirring, and then refluxed at 80° C. for 8 h to obtain vanillic acid-furfurylamine benzoxazine (VF);
[0067] Step (3) Preparation of binary benzoxazine derivative monomer
[0068] First, 1 g of phenylphosphate bismaleimide was weighed using an electronic analytical balance and subjected to a Diels-Alder reaction. Then, 2 g of furfuryl alcohol resin and 1 g of vanillic acid-furfurylamine benzoxazine (VF) from step (2) were weighed and mixed together in a transparent glass vial and ultrasonically stirred. The mixture was placed in an oven at 70°C for 24 h to obtain a binary benzoxazine derivative monomer.
[0069] Step (4) Preparation of refined sodium carboxymethyl cellulose (CMC)
[0070] Concentrated nitric acid was diluted with anhydrous ethanol to a concentration of 25% to obtain a nitric acid ethanol solution. 10 g of CMC powder (sodium carboxymethyl cellulose) was weighed and dissolved in the nitric acid ethanol solution. The reaction lasted for 2 hours and then filtered. The insoluble matter obtained was CMC-H. The CMC-H was washed with deionized water for several times until the pH of CMC-H was 6. The above CMC-H was added to a 40% sodium hydroxide solution and stirred thoroughly to obtain a viscous transparent liquid. At this time, CMC- H and sodium oxide react to generate CMC (sodium carboxymethyl cellulose). CMC (sodium carboxymethyl cellulose) is viscous in water. 100 mL of the dibenzoxazine derivative monomer of step (3) is added to obtain a white flocculent, namely CMC (sodium carboxymethyl cellulose). The CMC (sodium carboxymethyl cellulose) is washed once with a 70% by volume ethanol solution until the pH is neutral, and then dried in a vacuum oven at 100°C to constant weight for about 4 hours. After crushing, refined sodium carboxymethyl cellulose (CMC) is obtained.
[0071] Step (5) Preparation of water-soluble bio-based carbon-forming agent
[0072] Melamine (MA) and vanillin are added to a flask in a ratio of 1:2, and then 10 g of dimethylformamide (DMF) solvent is added, and the reaction is stirred for 2 h. After the reaction is complete, the reaction temperature is increased until dimethylformamide (DMF) is volatilized, and the solution after the reaction is poured out and dried to obtain a bio-based carbon-forming agent carbon coating (MV). 10 g of the refined sodium carboxymethyl cellulose (CMC) in step (4) is added to a beaker, and the solution is stirred to mix evenly. 1:1 ammonium polyphosphate (APP) is added and stirred for 1 h. Finally, the obtained solution is dried and crushed to obtain a water-soluble bio-based carbon-forming agent.
[0073] Step (6) Preparation of smoke-suppressing, low-toxicity, flame-retardant liquid PAP-Mg-Na
[0074] First, PAPEMP (polyaminopolyether methylenephosphonic acid) was used as an organic ligand to prepare a 50 wt% ligand solution. The metal salt MgCl2·6H20 was dissolved in tap water to obtain a 20 w% metal solution. The two solutions were mixed in a 1:1 mass ratio and stirred at room temperature for 30 min. Then, 10 g of the water-soluble bio-based carbon-forming agent from step (5) was added to promote the ligand to react with the metal ion Mg. 2+ A complexing reaction occurs to obtain a complexing solution, and then a NaOH promoting solution is added and slowly added to the complexing solution and stirred for 10 minutes to obtain a smoke-suppressing, low-toxicity, flame-retardant liquid PAP-Mg-Na;
[0075] Step (7) Preparation of complex flame retardant PAP-Ly-Mg
[0076] Lysine, ammonium polyphosphate (APP) and melamine were added into a four-necked flask in a molar ratio of 1:2:3, mixed and stirred, heated to 300°C with a constant temperature digital display heating mantle, added with 10 mL of the smoke-suppressing and low-toxic flame-retardant liquid PAP-Mg-Na prepared in step (6), and then added with 10 g of chitosan and vitamin B, and after curing, ripened for 60 min, and crushed to obtain a complex flame retardant PAP-Ly-Mg;
[0077] Step (8) Preparation of MOF (metal organic framework) flame retardant composite materials
[0078] 0.1 g of dried MOFs (metal organic framework) nanoparticles were ultrasonically dispersed in 30 mL of ethanol solution, and 10 mL of the complex flame retardant PAP-Ly-Mg in step (7) was added to the above liquid. The mixture was allowed to stand for 30 min and then added to 150 mL of cellulose dispersion. The mixture was vigorously stirred at room temperature for 4 h. The water was removed from the mixture through a Buchner funnel and then dried in a vacuum oven at 80 ° C for 24 h to obtain a MOF (metal organic framework) flame retardant composite material.
[0079] Example 2
[0080] Step (1) Preparation of dioxane
[0081] In a 270 mL round-bottom flask, add 120 g of diethylene glycol and 2.5 g of anhydrous copper sulfate, heat the reaction flask to keep it boiling, control the heating for 2 h, and after the reaction is completed, cool to room temperature, add 110 g of diethylene glycol to the reaction flask, continue heating, collect the distillate, add 15 mL of concentrated hydrochloric acid to the distillate, and then reflux to remove acetal impurities, separate the water layer after post-treatment, dry the oil layer, and collect the distillate with a boiling point of 110 ° C by distillation to obtain dioxane;
[0082] Step (2) Preparation of vanillic acid-furfurylamine benzoxazine (VF)
[0083] 17 g of the dioxane prepared in step (1), 10 g of furfurylamine (0.13 mol) and 7 g of paraformaldehyde were added to a three-necked flask in sequence, and then 92 mL of a toluene / ethanol mixed solution was added. The raw materials were uniformly mixed by stirring, and then refluxed at 83 ° C for 9 h to obtain vanillic acid-furfurylamine benzoxazine (VF);
[0084] Step (3) Preparation of binary benzoxazine derivative monomer
[0085] First, 2 g of phenylphosphate bismaleimide was weighed using an electronic analytical balance and subjected to a Diels-Alder reaction. Then, 4 g of furfuryl alcohol resin and 2 g of vanillic acid-furfurylamine benzoxazine (VF) from step (2) were weighed and mixed together in a transparent glass vial and ultrasonically stirred. The mixture was placed in an oven at 75°C for 29 h to obtain a binary benzoxazine derivative monomer.
[0086] Step (4) Preparation of refined sodium carboxymethyl cellulose (CMC)
[0087] Concentrated nitric acid was diluted with anhydrous ethanol to a concentration of 27% to obtain a nitric acid ethanol solution. 13g of CMC powder (sodium carboxymethyl cellulose) was weighed and dissolved in the nitric acid ethanol solution. The reaction lasted for 2.5h and then filtered. The insoluble matter obtained was CMC-H. The CMC-H was washed with deionized water for several times until the pH of CMC-H was 6.5. The above CMC-H was added to a 43% sodium hydroxide solution and stirred thoroughly to obtain a viscous transparent liquid. At this time, CMC -H reacts with sodium oxide to generate CMC (sodium carboxymethyl cellulose). CMC (sodium carboxymethyl cellulose) is viscous in water. 120 mL of the dibenzoxazine derivative monomer of step (3) is added to obtain a white flocculent, namely CMC (sodium carboxymethyl cellulose). CMC (sodium carboxymethyl cellulose) is washed twice with a 72% by volume ethanol solution until the pH is neutral, and then dried in a vacuum oven at 120°C to constant weight for about 4.5 hours. After crushing, refined sodium carboxymethyl cellulose (CMC) is obtained.
[0088] Step (5) Preparation of water-soluble bio-based carbon-forming agent
[0089] Melamine (MA) and vanillin are added to a flask at a ratio of 2:3, and then 13 g of dimethylformamide (DMF) solvent is added, and the reaction is stirred for 2.6 h. After the reaction is complete, the reaction temperature is increased until the dimethylformamide (DMF) is volatilized, and the solution after the reaction is poured out and dried to obtain a bio-based carbon-forming agent carbon coating (MV). 15 g of the refined sodium carboxymethyl cellulose (CMC) in step (4) is added to a beaker, and the solution is stirred to mix evenly. Ammonium polyphosphate (APP) is added at a ratio of 2:2, and the mixture is stirred for 2 h. Finally, the resulting solution is dried and crushed to obtain a water-soluble bio-based carbon-forming agent.
[0090] Step (6) Preparation of smoke-suppressing, low-toxicity, flame-retardant liquid PAP-Mg-Na
[0091] First, PAPEMP (polyaminopolyether methylenephosphonic acid) was used as an organic ligand to prepare a 60 wt% ligand solution. The metal salt MgCl2·6H20 was dissolved in tap water to obtain a 25 w% metal solution. The two solutions were then mixed in a mass ratio of 2:2 and stirred at room temperature for 34 min. Then, 14 g of the water-soluble bio-based carbon-forming agent from step (5) was added to promote the ligand to react with the metal ion Mg. 2+ A complexation reaction occurs to obtain a complexation solution, and then a NaOH promoting solution is added and slowly added to the complexation solution, and stirred for 19 minutes to obtain a smoke-suppressing, low-toxicity, flame-retardant liquid PAP-Mg-Na;
[0092] Step (7) Preparation of complex flame retardant PAP-Ly-Mg
[0093] Lysine, ammonium polyphosphate (APP) and melamine were added into a four-necked flask in a molar ratio of 2:3:4, mixed and stirred, heated to 350°C with a constant temperature digital display heating mantle, added with 19 mL of the smoke-suppressing and low-toxic flame-retardant liquid PAP-Mg-Na prepared in step (6), and then added with 19 g of chitosan and vitamin B, and after curing, ripened for 69 min, and crushed to obtain a complex flame retardant PAP-Ly-Mg;
[0094] Step (8) Preparation of MOF (metal organic framework) flame retardant composite materials
[0095] 0.19 g of dried MOFs (metal organic framework) nanoparticles were ultrasonically dispersed in 37 mL of ethanol solution, and 18 mL of the complex flame retardant PAP-Ly-Mg in step (7) was added to the above liquid. The mixture was allowed to stand for 40 min and then added to 200 mL of cellulose dispersion. The mixture was vigorously stirred at room temperature for 5 h. The water was removed from the mixture through a Buchner funnel and then dried in a vacuum oven at 88 ° C for 29 h to obtain a MOF (metal organic framework) flame retardant composite material.
[0096] Example 3
[0097] Step (1) Preparation of dioxane
[0098] In a 200 mL round-bottom flask, add 139 g of diethylene glycol and 3 g of anhydrous copper sulfate, heat the reaction flask to keep it boiling, control the heating for 3 h, and after the reaction is completed, cool to room temperature, add 120 g of diethylene glycol to the reaction flask, continue heating, collect the distillate, add 18 mL of concentrated hydrochloric acid to the distillate, and then reflux to remove acetal impurities, separate the water layer after post-treatment, dry the oil layer, and distill and collect the distillate with a boiling point of 139 ° C to obtain dioxane;
[0099] Step (2) Preparation of vanillic acid-furfurylamine benzoxazine (VF)
[0100] 19 g of the dioxane prepared in step (1), 13 g of furfurylamine (0.13 mol) and 9 g of paraformaldehyde were added to a three-necked flask in sequence, and then 98 mL of a toluene / ethanol mixed solution was added. The raw materials were uniformly mixed by stirring, and then refluxed at 89° C. for 13 h to obtain vanillic acid-furfurylamine benzoxazine (VF);
[0101] Step (3) Preparation of binary benzoxazine derivative monomer
[0102] First, 4 g of phenylphosphate bismaleimide was weighed using an electronic analytical balance and subjected to a Diels-Alder reaction. Then, 4 g of furfuryl alcohol resin and 4 g of vanillic acid-furfurylamine benzoxazine (VF) from step (2) were weighed and mixed together in a transparent glass vial and ultrasonically stirred. The mixture was placed in an oven at 85° C. for 35 h to obtain a binary benzoxazine derivative monomer.
[0103] Step (4) Preparation of refined sodium carboxymethyl cellulose (CMC)
[0104] Concentrated nitric acid was diluted with anhydrous ethanol to a concentration of 30% to obtain a nitric acid ethanol solution. 16 g of CMC powder (sodium carboxymethyl cellulose) was weighed and dissolved in the nitric acid ethanol solution. The reaction lasted for 3 hours and then filtered. The insoluble matter obtained was CMC-H. The CMC-H was washed with deionized water for several times until the pH of CMC-H was 8. The above CMC-H was added to a 49% sodium hydroxide solution and stirred thoroughly to obtain a viscous transparent liquid. At this time, CMC- H reacts with sodium oxide to generate CMC (sodium carboxymethyl cellulose). CMC (sodium carboxymethyl cellulose) is viscous in water. 140 mL of the dibenzoxazine derivative monomer of step (3) is added to obtain a white flocculent, namely CMC (sodium carboxymethyl cellulose). The CMC (sodium carboxymethyl cellulose) is washed 4 times with a 75% by volume ethanol solution until the pH is neutral, and then dried in a vacuum oven at 130°C to constant weight for about 5 hours. After crushing, refined sodium carboxymethyl cellulose (CMC) is obtained.
[0105] Step (5) Preparation of water-soluble bio-based carbon-forming agent
[0106] Melamine (MA) and vanillin are added to a flask in a ratio of 3:4, and then 16 g of dimethylformamide (DMF) solvent is added, and the reaction is stirred for 4 h. After the reaction is complete, the reaction temperature is increased until the dimethylformamide (DMF) is volatilized, and the solution after the reaction is poured out and dried to obtain a bio-based carbon-forming agent carbon coating (MV). 18 g of the refined sodium carboxymethyl cellulose (CMC) in step (4) is added to a beaker, and the solution is stirred to mix evenly. 4:4 ammonium polyphosphate (APP) is added and stirred for 4 h. Finally, the obtained solution is dried and crushed to obtain a water-soluble bio-based carbon-forming agent.
[0107] Step (6) Preparation of smoke-suppressing, low-toxicity, flame-retardant liquid PAP-Mg-Na
[0108] First, PAPEMP (polyaminopolyether methylenephosphonic acid) was used as an organic ligand to prepare a 62 wt% ligand solution. The metal salt MgCl2·6H20 was dissolved in tap water to obtain a 30 w% metal solution. The two solutions were mixed in a mass ratio of 3:3 and stirred at room temperature for 50 min. Then, 19 g of the water-soluble bio-based carbon-forming agent from step (5) was added to promote the ligand to react with the metal ion Mg. 2+ A complexing reaction occurs to obtain a complexing solution, and then a NaOH promoting solution is added and slowly added to the complexing solution, and stirred for 30 minutes to obtain a smoke-suppressing, low-toxic, flame-retardant liquid PAP-Mg-Na;
[0109] Step (7) Preparation of complex flame retardant PAP-Ly-Mg
[0110] Lysine, ammonium polyphosphate (APP) and melamine were added into a four-necked flask in a molar ratio of 3:4:5, mixed and stirred, heated to 400°C with a constant temperature digital display heating mantle, added with 23 mL of the smoke-suppressing and low-toxic flame-retardant liquid PAP-Mg-Na prepared in step (6), and then added with 39 g of chitosan and vitamin B, and after curing, ripened for 80 min, and crushed to obtain a complex flame retardant PAP-Ly-Mg;
[0111] Step (8) Preparation of MOF (metal organic framework) flame retardant composite materials
[0112] 0.4 g of dried MOFs (metal organic framework) nanoparticles were ultrasonically dispersed in 40 mL of ethanol solution, and 31 mL of the complex flame retardant PAP-Ly-Mg in step (7) was added to the above liquid. The mixture was allowed to stand for 48 minutes and then added to 210 mL of cellulose dispersion. The mixture was vigorously stirred at room temperature for 7 hours. The water was removed from the mixture through a Buchner funnel and then dried in a vacuum oven at 94°C for 36 hours to obtain a MOF (metal organic framework) flame retardant composite material.
[0113] Example 4
[0114] Step (1) Preparation of dioxane
[0115] In a 500mL round-bottom flask, add 200g of diethylene glycol and 5g of anhydrous copper sulfate, heat the reaction flask to keep it boiling, control the heating for 5h, after the reaction is completed, cool to room temperature, add 200g of diethylene glycol to the reaction flask, continue heating, collect the distillate, add 20mL of concentrated hydrochloric acid to the distillate, then reflux to remove acetal impurities, separate the water layer after post-treatment, dry the oil layer, and collect the distillate with a boiling point of 200°C by distillation to obtain dioxane;
[0116] Step (2) Preparation of vanillic acid-furfurylamine benzoxazine (VF)
[0117] 20 g of the dioxane prepared in step (1), 15 g of furfurylamine (1 mol) and 10 g of paraformaldehyde were added to a three-necked flask in sequence, and then 100 mL of a toluene / ethanol mixed solution was added. The raw materials were uniformly mixed by stirring, and then refluxed at 100° C. for 15 h to obtain vanillic acid-furfurylamine benzoxazine (VF);
[0118] Step (3) Preparation of binary benzoxazine derivative monomer
[0119] First, 5 g of phenylphosphate bismaleimide was weighed using an electronic analytical balance and subjected to a Diels-Alder reaction. Then, 6 g of furfuryl alcohol resin and 5 g of vanillic acid-furfurylamine benzoxazine (VF) from step (2) were weighed and mixed together in a transparent glass vial and ultrasonically stirred. The mixture was placed in an oven at 90° C. for 48 h to obtain a binary benzoxazine derivative monomer.
[0120] Step (4) Preparation of refined sodium carboxymethyl cellulose (CMC)
[0121] Concentrated nitric acid was diluted with anhydrous ethanol to a concentration of 35% to obtain a nitric acid ethanol solution. 20g of CMC powder (sodium carboxymethyl cellulose) was weighed and dissolved in the nitric acid ethanol solution. The reaction lasted for 5 hours and then filtered. The insoluble matter obtained was CMC-H. The CMC-H was washed with deionized water for several times until the pH of CMC-H was 10. The above CMC-H was added to a 50% sodium hydroxide solution and stirred thoroughly to obtain a viscous transparent liquid. At this time, CMC- H and sodium oxide react to generate CMC (sodium carboxymethyl cellulose). CMC (sodium carboxymethyl cellulose) is viscous in water. 200 mL of the dibenzoxazine derivative monomer of step (3) is added to obtain a white flocculent, namely CMC (sodium carboxymethyl cellulose). The CMC (sodium carboxymethyl cellulose) is washed 5 times with an ethanol solution with a volume fraction of 81% until the pH is neutral, and then dried in a vacuum oven at 150°C to constant weight for about 10 hours. After crushing, refined sodium carboxymethyl cellulose (CMC) is obtained.
[0122] Step (5) Preparation of water-soluble bio-based carbon-forming agent
[0123] Melamine (MA) and vanillin are added to a flask at a ratio of 5:5, and then 20 g of dimethylformamide (DMF) solvent is added, and the reaction is stirred for 5 h. After the reaction is complete, the reaction temperature is increased until the dimethylformamide (DMF) is volatilized, and the solution after the reaction is poured out and dried to obtain a bio-based carbon-forming agent carbon coating (MV). 20 g of the refined sodium carboxymethyl cellulose (CMC) in step (4) is added to a beaker, and the solution is stirred to mix evenly. 5:5 ammonium polyphosphate (APP) is added and the mixture is stirred for 5 h. Finally, the resulting solution is dried and crushed to obtain a water-soluble bio-based carbon-forming agent.
[0124] Step (6) Preparation of smoke-suppressing, low-toxicity, flame-retardant liquid PAP-Mg-Na
[0125] First, PAPEMP (polyaminopolyether methylenephosphonic acid) was used as an organic ligand to prepare a 69 wt% ligand solution. The metal salt MgCl2·6H20 was dissolved in tap water to obtain a 50 w% metal solution. The two solutions were mixed at a mass ratio of 5:5 and stirred at room temperature for 60 min. Then, 20 g of the water-soluble bio-based carbon-forming agent in step (5) was added to promote the ligand to react with the metal ion Mg. 2+ A complexing reaction occurs to obtain a complexing solution, and then a NaOH promoting solution is added and slowly added to the complexing solution, and stirred for 60 minutes to obtain a smoke-suppressing, low-toxicity, flame-retardant liquid PAP-Mg-Na;
[0126] Step (7) Preparation of complex flame retardant PAP-Ly-Mg
[0127] Lysine, ammonium polyphosphate (APP) and melamine were added into a four-necked flask in a molar ratio of 5:5:5, mixed and stirred, heated to 600°C with a constant temperature digital display heating mantle, added with 50 mL of the smoke-suppressing and low-toxic flame-retardant liquid PAP-Mg-Na prepared in step (6), and then added with 50 g of chitosan and vitamin B, and after curing, ripened for 120 min, and crushed to obtain a complex flame retardant PAP-Ly-Mg;
[0128] Step (8) Preparation of MOF (metal organic framework) flame retardant composite materials
[0129] 0.5 g of dried MOFs (metal organic framework) nanoparticles were ultrasonically dispersed in 60 mL of ethanol solution, and 50 mL of the complex flame retardant PAP-Ly-Mg in step (7) was added to the above liquid. The mixture was allowed to stand for 60 min and then added to 300 mL of cellulose dispersion. The mixture was vigorously stirred at room temperature for 10 h. The water was removed from the mixture through a Buchner funnel and then dried in a vacuum oven at 100 ° C for 48 h to obtain a MOF (metal organic framework) flame retardant composite material.
[0130] Comparative Example 1
[0131] Step (1) Preparation of binary benzoxazine derivative monomer
[0132] First, 8 g of phenylphosphate bismaleimide was weighed with an electronic analytical balance and subjected to Diels-Alder reaction, and then 8 g of furfuryl alcohol resin and 9 g of vanillic acid-furfurylamine benzoxazine (VF) were weighed, mixed together in a transparent glass vial and ultrasonically stirred, and placed in an oven at 99° C. for 46 hours to obtain a binary benzoxazine derivative monomer;
[0133] Step (2) Preparation of refined sodium carboxymethyl cellulose (CMC)
[0134] Concentrated nitric acid was diluted with anhydrous ethanol to a concentration of 70% to obtain a nitric acid ethanol solution. 90g of CMC powder (sodium carboxymethyl cellulose) was weighed and dissolved in the nitric acid ethanol solution. The reaction was performed for 8 hours and then filtered. The insoluble matter obtained at this time was CMC-H. The CMC-H was washed with deionized water for many times until the pH of CMC-H was 16. The above CMC-H was added to a sodium hydroxide solution with a concentration of 120% and stirred thoroughly to obtain a viscous transparent liquid. At this time, CMC- H and sodium oxide react to generate CMC (sodium carboxymethyl cellulose). CMC (sodium carboxymethyl cellulose) is viscous in water. 210 mL of the dibenzoxazine derivative monomer of step (1) is added to obtain a white flocculent, namely CMC (sodium carboxymethyl cellulose). CMC (sodium carboxymethyl cellulose) is washed 6 times with a 93% by volume ethanol solution until the pH is neutral, and then dried in a vacuum oven at 190°C to constant weight for about 11 hours. After crushing, refined sodium carboxymethyl cellulose (CMC) is obtained.
[0135] Step (3) Preparation of water-soluble bio-based carbon-forming agent
[0136] Melamine (MA) and vanillin are added to a flask at a ratio of 9:5, and then 28 g of dimethylformamide (DMF) solvent is added, and the reaction is stirred for 7 hours. After the reaction is complete, the reaction temperature is increased until the dimethylformamide (DMF) is volatilized, and the solution after the reaction is poured out and dried to obtain a bio-based carbon-forming agent carbon coating (MV). 23 g of the refined sodium carboxymethyl cellulose (CMC) in step (2) is added to a beaker, and the solution is stirred to mix evenly. 6:9 ammonium polyphosphate (APP) is added and the mixture is stirred for 8 hours. Finally, the resulting solution is dried and crushed to obtain a water-soluble bio-based carbon-forming agent.
[0137] Step (4) Preparation of smoke-suppressing, low-toxicity, flame-retardant liquid PAP-Mg-Na
[0138] First, PAPEMP (polyaminopolyether methylenephosphonic acid) was used as an organic ligand to prepare an 85 wt% ligand solution. The metal salt MgCl2·6H20 was dissolved in tap water to obtain a 50 w% metal solution. The two solutions were mixed at a mass ratio of 9:5 and stirred at room temperature for 66 min. Then, 20 g of the water-soluble bio-based carbon-forming agent from step (3) was added to promote the ligand to react with the metal ion Mg. 2+ A complexing reaction occurs to obtain a complexing solution, and then a NaOH promoting solution is added and slowly added to the complexing solution, and stirred for 60 minutes to obtain a smoke-suppressing, low-toxicity, flame-retardant liquid PAP-Mg-Na;
[0139] Step (5) Preparation of complex flame retardant PAP-Ly-Mg
[0140] Lysine, ammonium polyphosphate (APP) and melamine were added into a four-necked flask in a molar ratio of 6:5:7, mixed and stirred, heated to 670°C with a constant temperature digital display heating mantle, added with 50 mL of the smoke-suppressing and low-toxic flame-retardant liquid PAP-Mg-Na prepared in step (4), and then added with 57 g of chitosan and vitamin B, and after curing, ripened for 135 min, and crushed to obtain a complex flame retardant PAP-Ly-Mg;
[0141] Step (6) Preparation of MOF (metal organic framework) flame retardant composite materials
[0142] 0.7 g of dried MOFs (metal organic framework) nanoparticles were ultrasonically dispersed in 89 mL of ethanol solution, and 50 mL of the complex flame retardant PAP-Ly-Mg in step (7) was added to the above liquid. The mixture was allowed to stand for 69 minutes and then added to 390 mL of cellulose dispersion. The mixture was vigorously stirred at room temperature for 16 hours. The water was removed from the mixture through a Buchner funnel and then dried in a vacuum oven at 180°C for 49 hours to obtain a MOF (metal organic framework) flame retardant composite material.
[0143] Comparative Example 2
[0144] Step (1) Preparation of vanillic acid-furfurylamine benzoxazine (VF)
[0145] 24 g of dioxane, 18 g of furfurylamine (1 mol) and 16 g of paraformaldehyde were added to a three-necked flask in sequence, and then 109 mL of a toluene / ethanol mixed solution was added. The raw materials were uniformly mixed by stirring, and then refluxed at 121° C. for 16 h to obtain vanillic acid-furfurylamine benzoxazine (VF);
[0146] Step (2) Preparation of binary benzoxazine derivative monomer
[0147] First, 9 g of phenylphosphate bismaleimide was weighed using an electronic analytical balance and subjected to a Diels-Alder reaction. Then, 11 g of furfuryl alcohol resin and 14 g of vanillic acid-furfurylamine benzoxazine (VF) from step (2) were weighed and mixed together in a transparent glass vial and ultrasonically stirred. The mixture was placed in an oven at 103° C. for 60 h to obtain a binary benzoxazine derivative monomer.
[0148] Step (3) Preparation of refined sodium carboxymethyl cellulose (CMC)
[0149] Concentrated nitric acid was diluted with anhydrous ethanol to a concentration of 39% to obtain a nitric acid ethanol solution. 29g of CMC powder (sodium carboxymethyl cellulose) was weighed and dissolved in the nitric acid ethanol solution. The reaction lasted for 9 hours and then filtered. The insoluble matter obtained was CMC-H. The CMC-H was washed with deionized water for several times until the pH of CMC-H was 19. The above CMC-H was added to a sodium hydroxide solution with a concentration of 190% and stirred thoroughly to obtain a viscous transparent liquid. At this time, CMC- H and sodium oxide react to generate CMC (sodium carboxymethyl cellulose). CMC (sodium carboxymethyl cellulose) is viscous in water. 220 mL of the dibenzoxazine derivative monomer in step (2) is added to obtain a white flocculent, namely CMC (sodium carboxymethyl cellulose). The CMC (sodium carboxymethyl cellulose) is washed 8 times with a 95% by volume ethanol solution until the pH is neutral, and then dried in a vacuum oven at 200°C to constant weight for about 13 hours. After crushing, refined sodium carboxymethyl cellulose (CMC) is obtained.
[0150] Step (4) Preparation of water-soluble bio-based carbon-forming agent
[0151] Melamine (MA) and vanillin are added to a flask at a ratio of 7:9, and then 70 g of dimethylformamide (DMF) solvent is added, and the reaction is stirred for 9 hours. After the reaction is complete, the reaction temperature is increased until the dimethylformamide (DMF) is volatilized, and the solution after the reaction is poured out and dried to obtain a bio-based carbon-forming agent carbon coating (MV). 29 g of the refined sodium carboxymethyl cellulose (CMC) in step (3) is added to a beaker, and the solution is stirred to mix evenly. Ammonium polyphosphate (APP) is added at a ratio of 7:7, and the mixture is stirred for 9 hours. Finally, the resulting solution is dried and crushed to obtain a water-soluble bio-based carbon-forming agent.
[0152] Step (5) Preparation of smoke-suppressing, low-toxicity, flame-retardant liquid PAP-Mg-Na
[0153] First, PAPEMP (polyaminopolyether methylenephosphonic acid) was used as an organic ligand to prepare an 87 wt % ligand solution. The metal salt MgCl2·6H20 was dissolved in tap water to obtain a 59 w % metal solution. The two solutions were mixed in a mass ratio of 8:9 and stirred at room temperature for 78 min. Then, 28 g of the water-soluble bio-based carbon-forming agent from step (4) was added to promote the ligand to react with the metal ion Mg. 2+ A complexation reaction occurs to obtain a complexation solution, and then a NaOH promoting solution is added and slowly added to the complexation solution, and stirred for 89 minutes to obtain a smoke-suppressing, low-toxicity, flame-retardant liquid PAP-Mg-Na;
[0154] Step (6) Preparation of complex flame retardant PAP-Ly-Mg
[0155] Lysine, ammonium polyphosphate (APP) and melamine were added into a four-necked flask in a molar ratio of 9:5:7, mixed and stirred, heated to 690°C with a constant temperature digital display heating mantle, added with 52 mL of the smoke-suppressing and low-toxic flame-retardant liquid PAP-Mg-Na prepared in step (5), and then added with 57 g of chitosan and vitamin B, and after curing, ripened for 190 min, and crushed to obtain a complex flame retardant PAP-Ly-Mg;
[0156] Step (7) Preparation of MOF (metal organic framework) flame retardant composite materials
[0157] 0.9 g of dried MOFs (metal organic framework) nanoparticles were ultrasonically dispersed in 90 mL of ethanol solution, and 59 mL of the complex flame retardant PAP-Ly-Mg in step (7) was added to the above liquid. The mixture was allowed to stand for 69 minutes and then added to 300 mL of cellulose dispersion. The mixture was vigorously stirred at room temperature for 19 hours. The water was removed from the mixture through a Buchner funnel and then dried in a vacuum oven at 190°C for 49 hours to obtain a MOF (metal organic framework) flame retardant composite material.
[0158] Comparison of detection experiments:
[0159] The green flame retardant plywood obtained in Examples 1 to 4 and Comparative Example Products 1 and 2 were tested. The specific testing methods are as follows:
[0160] Oxygen Index Test Method
[0161] The oxygen index refers to the minimum oxygen volume concentration required to maintain combustion of the prepared material during the combustion process, generally expressed as a percentage. If the oxygen index of the prepared material is greater than 21% in the test, it is not easy to spontaneously ignite in the air. If the oxygen index is higher, it means that the material is more difficult to burn and exhibits excellent flame retardancy. If it is lower than 21%, vice versa.
[0162] Moisture content test method
[0163] When the moisture content of the prepared plywood is too high, the moisture in the wood will dilute the adhesive, reduce the curing effect of the adhesive, and cause the bonding strength of the glue layer to decrease. When the moisture content is too low, the water absorption capacity of its internal fibers is enhanced, and the glue will be quickly absorbed into the wood, resulting in uneven distribution of glue on the wood surface and insufficient glue on the bonding surface. The international standard optimal moisture content range is 7%-12%. Within this range, the flexibility of the wood can be guaranteed, and a good environment can be provided for the adhesion and curing of the glue.
[0164] Table 1 Oxygen index test results
[0165] Example Oxygen index / % 1 27 2 24 3 23 4 22 Comparative Example 1 10 Comparative Example 2 5
[0166] As can be seen from Table 1, Example 1 is the best and Comparative Example 2 is relatively poor. The oxygen index of Example 1 is 27%, showing the best flame retardant performance. This is because melamine forms a dense expanded carbon layer during thermal decomposition, which effectively blocks heat conduction and oxygen entry, thereby delaying thermal degradation of the matrix and inhibiting the generation of volatile free formaldehyde. The oxygen index of Comparative Example 2 is only 5%, indicating that no effective flame retardant protective layer is formed. This is due to the lack of key charring and foaming components in the intumescent flame retardant system, which makes it impossible to effectively block heat and oxygen when heated, and has the worst flame retardant performance.
[0167] Table 2 Test results of moisture content test method
[0168] Example Moisture content / % 1 10 2 9 3 8 4 7 Comparative Example 1 4 Comparative Example 2 3
[0169] As can be seen from Table 2, Example 1 is the best and Comparative Example 2 is poor. The moisture content of Example 1 is 10%, which is in the middle value of the international standard optimal moisture content range (7%-12%). The wood has moderate flexibility, the adhesive is evenly distributed and the curing effect is best, the adhesive layer has high bonding strength, and therefore has the best adhesive performance. The moisture content of Comparative Example 2 is 3%, which is far below the standard range. The wood is too dry, the fiber's water absorption capacity is enhanced, resulting in rapid absorption of the glue, uneven distribution of the glue layer, and insufficient glue on the bonding surface, and the bonding strength is significantly reduced, so the performance is poor.
[0170] This specific embodiment is merely an explanation of the present invention, and it is not a limitation of the present invention. A person skilled in the art can make non-creative modifications to the present embodiment as needed after reading this specification. However, as long as it is within the scope of the claims of the present invention, it is protected by the patent law.
Claims
1. A preparation process of green flame retardant plywood, characterized in that: include: Preparation of dioxane, preparation of vanillic acid-furfurylamine benzoxazine (VF), preparation of binary benzoxazine derivative monomers, preparation of refined sodium carboxymethyl cellulose (CMC), preparation of water-soluble bio-based carbon-forming agent, preparation of smoke-suppressing and low-toxic flame-retardant liquid PAP-Mg-Na, preparation of complex flame retardant PAP-Ly-Mg, preparation of MOF (metal organic framework) flame-retardant composite materials; Wherein, step (3) preparation of binary benzoxazine derivative monomer First, a certain amount of phenylphosphate bismaleimide is weighed using an electronic analytical balance and subjected to a Diels-Alder reaction. Then, a small amount of furfuryl alcohol resin and a small amount of vanillic acid-furfurylamine benzoxazine (VF) in step (2) are weighed, mixed together in a transparent glass vial and ultrasonically stirred, and then placed in an oven at high temperature to obtain a binary benzoxazine derivative monomer; Step (6) Preparation of smoke-suppressing, low-toxicity, flame-retardant liquid PAP-Mg-Na First, PAPEMP (polyamino polyether methylene phosphonic acid) was used as an organic ligand to prepare a ligand solution. The metal salt MgCl2·6H20 was dissolved in tap water to obtain a metal solution. The two solutions were then mixed in a certain mass ratio and stirred at room temperature. The water-soluble bio-based carbon-forming agent in step (5) was then added to promote the ligand to react with the metal ion Mg. 2+ A complexing reaction occurs to obtain a complexing solution, and then a NaOH promoting solution is added and slowly added to the complexing solution with stirring to obtain a smoke-suppressing, low-toxic, flame-retardant liquid PAP-Mg-Na.
2. The preparation process of a green flame retardant plywood according to claim 1, characterized in that: Step (1) Preparation of dioxane In a round-bottom flask, add a certain amount of diethylene glycol and anhydrous copper sulfate, heat the reaction flask to keep it boiling, control the heating for a period of time, and after the reaction is completed, cool to room temperature, add a large amount of diethylene glycol to the reaction flask, continue heating, collect distillate, add a small amount of concentrated hydrochloric acid to the distillate, and then reflux to remove acetal impurities, separate the water layer after post-treatment, dry the oil layer, and collect the distillate by distillation to obtain dioxane; Step (2) Preparation of vanillic acid-furfurylamine benzoxazine (VF) A small amount of dioxane, furfurylamine and a small amount of paraformaldehyde from step (1) are added to a three-necked flask in sequence, and then a certain amount of toluene / ethanol mixed solution is added, and the raw materials are uniformly mixed by stirring, and then refluxed at high temperature for a period of time to obtain vanillic acid-furfurylamine benzoxazine (VF); Step (3) Preparation of binary benzoxazine derivative monomer First, a certain amount of phenylphosphate bismaleimide is weighed using an electronic analytical balance and subjected to a Diels-Alder reaction. Then, a small amount of furfuryl alcohol resin and a small amount of vanillic acid-furfurylamine benzoxazine (VF) in step (2) are weighed, mixed together in a transparent glass vial and ultrasonically stirred, and then placed in an oven at high temperature to obtain a binary benzoxazine derivative monomer; Step (4) Preparation of refined sodium carboxymethyl cellulose (CMC) The concentrated nitric acid is diluted with anhydrous ethanol to obtain a nitric acid ethanol solution, a small amount of CMC powder (sodium carboxymethyl cellulose) is weighed, and the CMC powder (sodium carboxymethyl cellulose) is dissolved in the nitric acid ethanol solution and filtered after reaction. The insoluble matter obtained at this time is CMC-H. The CMC-H is washed with deionized water for many times. The above CMC-H is added to a high concentration of sodium hydroxide solution and stirred thoroughly to obtain a viscous transparent liquid. At this time, CMC-H reacts with sodium oxide to generate CMC (sodium carboxymethyl cellulose). CMC (sodium carboxymethyl cellulose) is viscous in water. A large amount of the dibenzoxazine derivative monomer in step (3) is added to obtain a white flocculent, which is CMC (sodium carboxymethyl cellulose). The CMC (sodium carboxymethyl cellulose) is washed with an ethanol solution for many times until the pH is neutral, and then dried in a vacuum oven to constant weight. After crushing, refined sodium carboxymethyl cellulose (CMC) is obtained; Step (5) Preparation of water-soluble bio-based carbon-forming agent Melamine (MA) and vanillin are added to a flask in a certain ratio, and then dimethylformamide (DMF) solvent is added, and the reaction is stirred. After the reaction is complete, the reaction temperature is increased until dimethylformamide (DMF) is volatilized, and the solution after the reaction is poured out and dried to obtain a bio-based carbon-forming agent carbon coating (MV). The refined sodium carboxymethyl cellulose (CMC) in step (4) is added to a beaker, and the solution is stirred to mix evenly. Ammonium polyphosphate (APP) is added and stirred thoroughly. Finally, the obtained solution is dried, and the solution is crushed to obtain a water-soluble bio-based carbon-forming agent; Step (6) Preparation of smoke-suppressing, low-toxicity, flame-retardant liquid PAP-Mg-Na First, PAPEMP (polyamino polyether methylene phosphonic acid) was used as an organic ligand to prepare a ligand solution. The metal salt MgCl2·6H20 was dissolved in tap water to obtain a metal solution. The two solutions were then mixed in a certain mass ratio and stirred at room temperature. The water-soluble bio-based carbon-forming agent in step (5) was then added to promote the ligand to react with the metal ion Mg. 2+ A complexing reaction occurs to obtain a complexing solution, and then a NaOH promoting solution is added and slowly added to the complexing solution with stirring to obtain a smoke-suppressing, low-toxic, flame-retardant liquid PAP-Mg-Na; Step (7) Preparation of complex flame retardant PAP-Ly-Mg Lysine, ammonium polyphosphate (APP) and melamine are added into a four-necked flask in a certain molar ratio, mixed and stirred, heated to a high temperature by a constant temperature digital display heating jacket, and a small amount of smoke-suppressing and low-toxic flame-retardant liquid PAP-Mg-Na prepared in step (6) is added, and chitosan and vitamin B are added, and after curing and ripening reaction, the mixture is crushed to obtain a complex flame retardant PAP-Ly-Mg; Step (8) Preparation of MOF (metal organic framework) flame retardant composite materials A small amount of dry MOFs (metal organic framework) nanoparticles is ultrasonically dispersed in an ethanol solution, and then the complex flame retardant PAP-Ly-Mg in step (7) is added to the above liquid, allowed to stand, and then added to the cellulose dispersion, vigorously stirred at room temperature, the mixed solution is drained through a Buchner funnel, and then dried in a vacuum oven to obtain a MOF (metal organic framework) flame retardant composite material.
3. The preparation process of a green flame retardant plywood according to claim 2, characterized in that: Step (1) Preparation of dioxane In a 250-500mL round-bottom flask, add 100-200g of diethylene glycol and 2-5g of anhydrous copper sulfate, heat the reaction flask to keep it boiling, control the heating for 1-5h, after the reaction is completed, cool to room temperature, add 105-200g of diethylene glycol to the reaction flask, continue heating, collect the distillate, add 10-20mL of concentrated hydrochloric acid to the distillate, and then reflux to remove acetal impurities, separate the water layer after post-treatment, dry the oil layer, and distill and collect the distillate with a boiling point of 100-200°C to obtain dioxane.
4. The process for preparing a green flame retardant plywood according to claim 3, characterized in that: Step (2) Preparation of vanillic acid-furfurylamine benzoxazine (VF) 16-20 g of the dioxane prepared in step (1), 9-15 g of furfurylamine (0.1-1 mol) and 6-10 g of paraformaldehyde are added to a three-necked flask in sequence, and then 90-100 mL of a toluene / ethanol mixed solution is added. The raw materials are uniformly mixed by stirring, and then refluxed at 80-100° C. for 8-15 h to obtain vanillic acid-furfurylamine benzoxazine (VF).
5. The process for preparing a green flame retardant plywood according to claim 4, characterized in that: Step (3) Preparation of binary benzoxazine derivative monomer First, 1-5 g of phenylphosphate bismaleimide is weighed on an electronic analytical balance and subjected to a Diels-Alder reaction. Then, 2-6 g of furfuryl alcohol resin and 1-5 g of vanillic acid-furfurylamine benzoxazine (VF) of step (2) are weighed, mixed together in a transparent glass vial and ultrasonically stirred, and then placed in an oven at 70-90° C. for 24-48 hours to obtain a binary benzoxazine derivative monomer.
6. The process for preparing a green flame retardant plywood according to claim 5, characterized in that: Step (4) Preparation of refined sodium carboxymethyl cellulose (CMC) Concentrated nitric acid is diluted with anhydrous ethanol to a concentration of 25-35% to obtain nitric acid ethanol solution. 10-20g of CMC powder (sodium carboxymethyl cellulose) is weighed and dissolved in the nitric acid ethanol solution. The reaction is carried out for 2-5h and then filtered. The insoluble matter obtained at this time is CMC-H. The CMC-H is washed with deionized water for many times until the pH of CMC-H is 6-10. The above CMC-H is added to a sodium hydroxide solution with a concentration of 40-50% and stirred thoroughly to obtain a viscous transparent liquid. At this time, CMC-H The obtained product is reacted with sodium oxide to generate CMC (sodium carboxymethyl cellulose). CMC (sodium carboxymethyl cellulose) is viscous in water. 100-200 mL of the dibenzoxazine derivative monomer of step (3) is added to obtain a white flocculent product, namely CMC (sodium carboxymethyl cellulose). The CMC (sodium carboxymethyl cellulose) is washed 1-5 times with an ethanol solution having a volume fraction of 70-85% until the pH is neutral, and then dried in a vacuum oven at 100-150°C to constant weight for about 4-10 hours. The refined sodium carboxymethyl cellulose (CMC) is obtained after being crushed.
7. The process for preparing green flame retardant plywood according to claim 6, characterized in that: Step (5) Preparation of water-soluble bio-based carbon-forming agent Melamine (MA) and vanillin are added to a flask at a ratio of 1-5:2-5, and then 10-20g of dimethylformamide (DMF) solvent is added, and the reaction is stirred for 2-5h. After the reaction is complete, the reaction temperature is increased until the dimethylformamide (DMF) is volatilized, and the solution after the reaction is poured out and dried to obtain a bio-based carbon-forming agent carbon coating (MV). 10-20g of the refined sodium carboxymethyl cellulose (CMC) in step (4) is added to a beaker, and the solution is stirred to mix evenly. Ammonium polyphosphate (APP) is added at a ratio of 1-5:1-5, and the mixture is stirred for 1-5h. Finally, the resulting solution is dried, and the solution is crushed to obtain a water-soluble bio-based carbon-forming agent.
8. The process for preparing green flame retardant plywood according to claim 7, characterized in that: Step (6) Preparation of smoke-suppressing, low-toxicity, flame-retardant liquid PAP-Mg-Na First, PAPEMP (polyamino polyether methylene phosphonic acid) is used as an organic ligand to prepare a 50-70 wt% ligand solution, and the metal salt MgCl2·6H20 is dissolved in tap water to obtain a 20-50 w% metal solution. The two solutions are then mixed in a mass ratio of 1-5:1-5, stirred at room temperature for 30-60 min, and then 10-20 g of the water-soluble bio-based carbon-forming agent in step (5) is added to promote the ligand to react with the metal ion Mg. 2+ A complexing reaction occurs to obtain a complexing solution, and then a NaOH promoting solution is added and slowly added to the complexing solution and stirred for 10-60 minutes to obtain a smoke-suppressing, low-toxicity, flame-retardant liquid PAP-Mg-Na.
9. The process for preparing green flame retardant plywood according to claim 8, characterized in that: Step (7) Preparation of complex flame retardant PAP-Ly-Mg Lysine, ammonium polyphosphate (APP) and melamine are added into a four-necked flask in a molar ratio of 1-5:2-5:3-5, mixed and stirred, heated to 300-600°C with a constant temperature digital display heating mantle, added with 10-50 mL of the smoke-suppressing and low-toxic flame-retardant liquid PAP-Mg-Na in step (6), and then added with 10-50 g of chitosan and vitamin B, and after curing, ripened for 60-120 min, and crushed to obtain a complex flame retardant PAP-Ly-Mg.
10. The process for preparing green flame retardant plywood according to claim 9, characterized in that: Step (8) Preparation of MOF (metal organic framework) flame retardant composite materials 0.1-0.5 g of dried MOFs (metal organic framework) nanoparticles are ultrasonically dispersed in 30-60 mL of ethanol solution, and then 10-50 mL of the complex flame retardant PAP-Ly-Mg in step (7) is added to the above liquid. The mixture is allowed to stand for 30-60 minutes and then added to 150-300 mL of cellulose dispersion. The mixture is vigorously stirred at room temperature for 4-10 hours. The water is removed from the mixture through a Buchner funnel and then dried in a vacuum oven at 80-100° C. for 24-48 hours to obtain a MOF (metal organic framework) flame retardant composite material.
Citation Information
Patent Citations
Wood flame-retardant and smoke-suppressant agent and preparation method thereof
CN110053121A
Production technology for continuous preparing 1,4-dioxane
CN1165137A
Synthesis process of smoke suppression biomass-based phosphorus-containing flame retardant
CN118755487A
Modified water-resistant smoke-suppressing low-toxicity adhesive as well as preparation method and application of modified water-resistant smoke-suppressing low-toxicity adhesive
CN118853044A